Worldwide study on field trials of biotechnological crops: new promises but old policy hurdles - Ricroch, Agnès; Desachy, Louie-David; Penfornis, Mateo; Akin, Melekşen; Kondić-Špika, Ankica; Kuntz, Marcel; Miladinović, Dragana (Frontiers in Plant Science, 2024)
Field trials (FTs) are a necessary step towards future commercialization of biotech crops and products thereof, whether for research and development or cultivation approval. A total of 187 FTs in 30 countries have been compiled for 2022 and 2023 using a survey and intergovernmental databases. FTs have been classified according to methods, crops and traits. Compiled FTs are mostly conducted by the public sector on eight plant species with improved stress resistance, industrial application, yield, and quality. Regarding genome editing (GenEd), 23 FTs (12% of total) are carried out in 6 countries, on 10 crops. Regulations were examined in 141 countries to discuss why in some countries FTs are not performed, although basic biotech research is carried out. The EU particularly is compared to the rest of the world. Regarding the new proposal in the EU for GenEd product classification, it was found that all recent FTs of such products fall in the category that the EU would consider as ‘equivalent to conventional plants’ (NGT-1). We also studied current cultivation approvals to highlight differences with crops tested in the field and those may be approved in the future.